Size and lipid content of nonmyrmecochorous diaspores: Effects on the interaction with litter-foraging ants in the Atlantic rain forest of Brazil - Pizo, Marco A. [UNESP]; Oliveira, Paulo S. (Springer Nature, 2001)
Ants are often attracted to diaspores not adapted for dispersal by ants. These diaspores may occasionally benefit from this interaction. We selected six nonmyrmecochorous plant species (Virola oleifera, Eugenia stictosepala, Cabralea canjerana, Citharexylum myrianthum, Alchornea glandulosa and Hyeronima alchorneoides) whose diaspores differ in size and lipid content, and investigated how these features affect the outcome of ant-diaspore interactions on the floor of a lowland Atlantic forest of Southeast Brazil. A total of 23 ant species were seen interacting with diaspores on the forest floor. Ants were generally rapid at discovering and cleaning the diaspore pulp or aril. Recruitment rate and ant attendance were higher for lipid-rich diaspores than for lipid-poor ones. Removal rate and displacement distance were higher for small diaspores. The large ponerine ant Pachycondyla striata, one of the most frequent attendants to lipid-rich arillate diaspores, transported the latter into their nests and discarded clean intact seeds on refuse piles outside the nest. Germination tests with cleaned and uncleaned diaspores revealed that the removal of pulp or aril may increase germination success in Virola oleifera, Cabralea canjerana, Citharexylum myrianthum and Alchornea glandulosa. Gas chromatography analyses revealed a close similarity in the fatty acid composition of the arils of the lipid-rich diaspores and the elaiosome of a typical myrmecochorous seed (Ricinus communis), corroborating the suggestion that some arils and elaiosomes are chemically similar. Although ant-derived benefits to diaspores - secondary dispersal and/or increased germination - varied among the six plant species studied, the results enhanced the role of ant-diaspore interactions in the post-dispersal fates of nonmyrmecochorous seeds in tropical forests. The size and the lipid-content of the diaspores were shown to be major determinants of the outcome of such interactions.
Keywords: Ant behaviour; Ant-plant interaction; Atlantic forest; Brazil; Myrmecochory; Seed dispersal; ant; lipid; plant-insect interaction; propagule; seed dispersal; size effect; zoochory; Alchornea; Alchornea glandulosa; Animalia; Cabralea; Cabralea canjerana; Citharexylum; Citharexylum myrianthum; Eugenia; Eugenia stictosepala; Formicidae; Hyeronima; Hyeronima alchorneoides; Hymenoptera; Insecta; Pachycondyla striata; Ricinus communis; Virola; Virola oleifera